ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9054716
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Video Coding and Super-Resolution for Efficient Delivery of 8k Video with 4k Backward-Compatibility

Abstract: In this paper, we propose, through an objective study, to compare and evaluate the performance of different coding approaches allowing the delivery of an 8K video signal with 4K backwardcompatibility on broadcast networks. Presented approaches include simulcast of 8K and 4K single-layer signals encoded using High-Efficiency Video Coding (HEVC) and Versatile Video Coding (VVC) standards, spatial scalability using SHVC with 4K base layer (BL) and 8K enhancement-layer (EL), and super-resolution applied on 4K VVC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Recently, a study was conducted to evaluate different scenarios for 8K video delivery with 4K backward compatibility relaying on objective quality metrics [16]. It was shown that .…”
Section: Related Workmentioning
confidence: 99%
“…Recently, a study was conducted to evaluate different scenarios for 8K video delivery with 4K backward compatibility relaying on objective quality metrics [16]. It was shown that .…”
Section: Related Workmentioning
confidence: 99%
“…Besides, Ho et al [19] proposed a degradation-aware technique which employs the original low-resolution (LR) as a transitional ground-truth to remove the degradation from compression and downsampling together. More recently, B. Charles et al [20][21] applied the same DBVC ideas based on the latest standard H.266/VVC, which shows a promising coding performance in low bitrate scenarios. Inspired by these successful DBVC methods for conventional 2D video coding, we design a new DBVC framework for LF data.…”
Section: Downsampling-based Video Coding (Dbvc)mentioning
confidence: 99%
“…The input signal is first downscaled and encoded. Then, both post-processing tasks are performed on the decoded signal outside the coding loop, as presented in [4] for super-resolution. The bit-rate is assessed on the low-resolution signal.…”
Section: Coding Performancementioning
confidence: 99%
“…In parallel, video processing deep learning-based solutions have been developed in order to reach these requirements and accelerate the deployment of these new services. For instance, the authors in [4] have proposed a backward-compatible solution for 8K and 4K signals broadcast using VVC and super-resolution. In [5], a feed-forward network is used as an in-loop filter to enhance the quality of the VVC decoded frames.…”
Section: Introductionmentioning
confidence: 99%